N-Carbamylglutamate Improves Reproductive Performance and Alters Fecal Microbiota and Serum Metabolites of Primiparous Sows during Gestation after Fixed-Time Artificial Insemination - Tao Feng; Linli Xiao; Jiahua Bai; Hongxiang Ding; Liyan Pang; Yuqing Song; Yusheng Qin; Xiaoling Xu; Jing Wang; Yan Liu (Biology, 2022)
N-carbamylglutamate (NCG) supplementation during gestation improves reproductive performance in sows after conventional artificial insemination. However, whether NCG can improve reproductive performance and change fecal microbiota and serum metabolite levels during pregnancy in sows after fixed-time artificial insemination (FTAI) remains unclear. Two hundred multiparous sows were assigned a diet from mating until farrowing: control (corn–soybean meal) or NCG supplementation (0.05% NCG). At days 30, 70, and 110 of gestation and after farrowing, maternal microbial diversity and serum metabolites were studied. Supplementation of NCG increased the number of piglets born alive and the litter weight (all p < 0.05) and altered the fetal microbial community during gestation. Some genera were particularly abundant at different time points during gestation and after farrowing, but none were commonly abundant across all four time points. Metabolic analysis revealed that NCG supplementation significantly increased the serum concentrations of NCG, ferulic acid, cinnamoylglycine, 3-phenyllactic acid, and gamma-glutamylglutamic acid in the NCG group compared with levels in the control group. Our results reveal that NCG supplementation during gestation improves reproductive performance in sows after FTAI, exerting both direct (increased serum NCG levels) and indirect effects (altered intestinal microbiome and serum metabolites) on sow reproduction and, ultimately, improving placental and fetal development.